Neonatal Research Network of Japan and Neonatal Database - Satoshi Kusuda (Korean Society of Neonatology, 2023)
In 2004, the Neonatal Research Network of Japan initiated a database registration system for high-risk infants in Japan. Currently, 65% of all very low the birth weight infants or infants born at <32 weeks of gestation are registered in the database. Approximately 4,000 new cases are registered annually. A unique feature of the database is that it includes outcome data at 1.5, 3, and 6 years after discharge from neonatal intensive care units. All registered data are fed back annually to the participating hospitals and used to benchmark neonatal care. Results from this database have also been published in many international journals. With the development of this database, neonatal medicine in Japan has progressed.